A Semantic Analysis of Slang Words Used by Gen Z on Social Media - Devita Pingkan Sitohang; Bernieke Anggita Ristia (Young Journal of Social Sciences and Humanities, 2025)
This study explores the semantic shifts and pragmatic functions of slang words used by Generation Z on social media platforms such as TikTok, Instagram, and Twitter. Employing a qualitative-descriptive approach, the research analyzes primary data collected through content analysis and ethnographic interviews with Gen Z users. The findings reveal that slang words used by Gen Z undergo various semantic changes such as pejoration, amelioration, metaphorical extension, and narrowing driven by cultural, technological, and contextual factors. These linguistic innovations not only reflect the evolving communication style of youth but also serve as tools for identity formation, humor, emotional expression, and social bonding in digital spaces. The study contributes to a deeper understanding of language dynamics in digital culture and offers insights into the mechanisms of semantic change in contemporary slang.